Pendidikan Matematika dalam Kontek Studi Islam: Al-Khwarizmi dan Kontribusinya untuk Matematika - Cahyo, Hariris Nur; Firmansyah, Ilham Nur (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2020)
This article aims to describe the role of Al-Khwarizmi and his contributions to mathematics and mathematics education in the context of Islamic studies. This research is a qualitative literature study. The approach used is the empirical historical approach because the historical approach must be understood as a type of empirical, empirical approach, especially in the sense where this term is contrasted with an apriorist, rationalistic, or intellectualist orientation. Reflexive methods such as narrative inquiry, autoetnography, joint ethnography, and community dialogue methods. As a form of understanding, narrative inquiry helps us shape our understanding of complex world events. In the study of history, the attention of observers drawn by the charm peculiar to the era gained prominence as greats in science and in every art of peace as they had achieved on the battlefield. Such times, in the history of the Arabs, were the Caliph Al Mansur, Harun Al Rashid, and Al Mamun, famous contemporaries of Charlemagne. From the results of the discussion it can be concluded as follows: 1) Science and mathematics in the modern world benefit from the contribution of Islamic culture, despite the frequent tacit denial (which has characterized the history of Western ideas since the 17th century) that Muslim thinkers and medieval scholars make a significant contribution to our understanding of the world. 2) Since the beginning Islamic education has always been the main religious education, in the sense that it is explicitly meant to preserve religious traditions and at the same time, there is a strong urge to seek knowledge in culture, such as the hadith